Isolation, genomic characterization and biotechnological evaluation of lactobacilli strains from chicken gastrointestinal tract - Bedir, Esra; Ay, Hilal; Kotil, Enes Seyfullah; Ozbek, Tulin (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2025)
During a study investigating possible probiotics from chicken gut microbiota, strains C1-4 and C2-3 were isolated and identified as members of the genus Ligilactobacillus. The strains formed a well-supported cluster with Ligilactobacillus salivarius and Ligilactobacillus hayatikensis in phylogenetic trees. Their genomes, sized 1.8 Mb with G + C content of 32 %, were related to Candidatus Avacholeplasma faecigallinarum with a dDDH level of 95.4 %, indicating the strains were the first culturable members of the uncultured taxon. Furthermore, a dDDH value of 78.9 % with L. salivarius DSM 20555T suggested that the strains may represent a novel subspecies of L. salivarius. The functional analysis of the genomes revealed that the strains harbour genes associated with probiotic traits, including lactate utilization, acetoin and butanediol metabolism, pH homeostasis and exopolysaccharide biosynthesis. The genome annotation for the secondary metabolite biosynthesis gene clusters showed that the strains have a type III polyketide gene cluster and a bacteriocin immunity protein gene. The strains exhibited phenotypic features compatible with their potential use as probiotics, such as tolerance to low pH and NaCl, ability to achieve high auto-aggregation, and hydrophobicity properties. In addition, the strains exhibited strong antibacterial activity against pathogenic MRSA (Meticillin-resistant Staphylococcus aureus ATCC 67101), S. aureus ATCC 25923, Listeria monocytogenes MBG16, and VRSA (Vancomycin-resistant Staphylococcus aureus MBG89), while showing moderate activity against Salmonella Typhimurium MBG15, Escherichia coli ATCC 25922, Klebsiella pneumoniae ATCC 13833, and Pseudomonas aeruginosa ATCC 27853. The cell-free supernatant of the strains notably affected Lis. monocytogenes and S. aureus, possibly due to possible bacteriocin production. In conclusion, the strains isolated from chicken gut microbiota have a high potential to be used as probiotics in agriculture and medicine.
Keywords: Probiotics; Ligilactobacillus salivarius; Bacteriocins; Antibiotic resistance; Antimicrobial peptides; PROBIOTIC CHARACTERISTICS; IN-VITRO; ESCHERICHIA-COLI; BACTERIA; SALIVARIUS; SEQUENCE; SAFETY; CLASSIFICATION; Immunology; Microbiology